THE POTENTIAL OF THE SHARIAH MICRO FINANCE INSTITUTION IN BUILDING THE UMMAT ECONOMY - Hendra (Az-Zahra Media Society, 2025)
As for the objective of this research, which is to outline the potential for optimization of LKMS (Shariah Micro Financial Institution) to assist in the building of the economy through the implementation of Shariah finance. Using qualitative descriptive approaches (interactive models) from a variety of previously published material such as articles, books, or journals of past study. The findings of the debate indicate that there is an increase tendency in terms of assets and loans/financing shown by OJK data for the period 2019 to 2023. In light of this, it may be deduced that the presence of LKMS has a considerable impact on the rate at which sustainable economic growth occurs. As a result, the part that Shariah micro-financial institutions played in the development of the economy in Indonesia turned out to be significant and pertinent. LKMS is the best answer for microentrepreneurs in situations in which they do not have access to microfinance from traditional banking institutions.